2018
DOI: 10.3961/jpmph.17.146
|View full text |Cite
|
Sign up to set email alerts
|

Peer Smoking and Smoking-related Beliefs Among College Students in Bangladesh

Abstract: ObjectivesSmoking is a significant public health issue in Bangladesh. The purpose of this study was to examine peer smoking and smoking-related beliefs among college students in Bangladesh.MethodsCollege students at two universities in Dhaka, Bangladesh participated in a self-administered survey in May and June 2017.ResultsFirst, being a current or former smoker is associated with lower levels of beliefs among respondents that they would not smoke even with smoker friends or nervousness, and lower levels of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
1
13
0
2
Order By: Relevance
“…The approval of being a peer support among those who have knowledge of SHS is consistent with a recent study (Kamimura, Ahmmad, Pye, & Gull, 2018). It is postulated that the reason behind this may be related to the idea that current or former smokers have a higher level of belief that they would smoke in front of colleagues.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The approval of being a peer support among those who have knowledge of SHS is consistent with a recent study (Kamimura, Ahmmad, Pye, & Gull, 2018). It is postulated that the reason behind this may be related to the idea that current or former smokers have a higher level of belief that they would smoke in front of colleagues.…”
Section: Discussionsupporting
confidence: 87%
“…It is postulated that the reason behind this may be related to the idea that current or former smokers have a higher level of belief that they would smoke in front of colleagues. Similarly, those smokers are more likely to smoke if their friends smoke, vice versa (Kamimura et al, 2018). This highlights the importance of the effects of social networks on smoking.…”
Section: Discussionmentioning
confidence: 84%
“…Evidence suggests that a strong and robust social disapproval method is important to suppress smoking behavior in public places. 39 , 44 Moreover, strengthening and complementing the smoke-free law with local policies provide a more promising outcome to improve compliance in all different types of designated smoke free venues and this combination of laws is expected to be able to change the smoking culture in the society which is the key to long-term compliance with smoke-free law. 45 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study on college students found smoking-related beliefs and norms recognized in individual social networks were important factors among smokers in Bangladesh [21]. Nonetheless, the reason many young people continue to smoke, and cannot stop smoking, is due to nicotine addiction.…”
Section: Discussionmentioning
confidence: 99%